Perceptions of auditees and banks regarding financial statement audits: a case for Portugal - Choon, Filipa Verissimo (2018)
KPMG (Direct Research Internship Programme) recommended the topic of the current empirical research, the objective of which is to uncover whether the market understands what auditing is, and if it recognizes the potential benefits of an (unqualified) audit report (e.g. to obtain more favourable loan conditions and to strengthen internal controls). The research also aims to uncover whether the market distinguishes on quality between the Big Four or a smaller firm. The results of the semi-structured interviews (with eight company executives and six elite bankers) reveal that some businesses carry out an audit solely to comply, with larger firms more likely to engage voluntarily. Consistent with the literature, banks advocate the superior quality of the Big Four, although many SMEs use smaller firms. As for lending, not all enterprises believe banks offer more favourable conditions, yet banks argue auditors’ unqualified opinion induce lower interest rates.